CHARACTER OF MALAY PATTANI COMMUNITY IN LITERARY WORK - Hajjah Djusmalinar (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
Culture shows tribes. This is no exception when we want to understand the Malay tribes residing in southern Thailand. Malay Muslim minority community which is very strong in practicing Malay culture in their daily lives. Unfortunately, this picture is not recorded in the form of architecture such as in the western countries, an idea of ​​the character of its people can be seen from several posts have ever been recorded in the form of literary works short stories and poems. This literary work is also not growing as expected because there are some obstacles. Some of these literature ever recorded in a magazine published in the 1970s and in the years 1980-1990 rhyme anthology's. Both materials are about character recorded Pattani Malay community as a source of reference in this study. It is because, literary works can be used as social documents to determine the character of a nation. This document will be analyzed by using sociology of literature, such as social background and the background of the community to know the character of the Pattani Malay community. Keywords: Sociology of Literature, Background, Malay, Pattani, and Character